2014
DOI: 10.3892/or.2014.3704
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3 (Dkk3) induces apoptosis in cisplatin-resistant lung adenocarcinoma cells via the Wnt/β-catenin pathway

Abstract: Abstract. Previous studies have shown that is inactivated in lung cancer cells, while the inactivation of the Wnt/β-catenin signaling pathway by Dkk3 inhibits lung cancer progression. In the present study, we investigated whether Dkk3 enhances the sensitivity of lung cancer cells to cisplatin. A549, Calu1 and H460 lung adenocarcinoma cell lines were transfected with DKK3 siRNA, while the cisplatin-resistant subline A549cis was transfected with DKK3. DKK3 expression was attenuated in A549cis, Calu1cis and H460c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Previous studies reported that several pathways are involved in β -catenin deficiency-induced cell death, including increased apoptosis of hepatic progenitor cells due to enhanced expression of cleaved caspase-9 and caspase-3 when β -catenin expression is blocked, 16 increased apoptosis in cisplatin-resistant lung adenocarcinoma cells when DKK3 is used to inhibit the Wnt/ β -catenin pathway, 35 and increased si-LGR5-induced apoptosis when the mitochondrial membrane potential is disrupted in colorectal cancer cells. 36 In our study, significantly greater HC loss was observed in β -catenin knockout cochleae compared with controls after neomycin treatment ( Figure 2 ), which was accompanied by upregulation of the pro-apoptotic transcription factor Foxo3 and its downstream target gene Bim ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that several pathways are involved in β -catenin deficiency-induced cell death, including increased apoptosis of hepatic progenitor cells due to enhanced expression of cleaved caspase-9 and caspase-3 when β -catenin expression is blocked, 16 increased apoptosis in cisplatin-resistant lung adenocarcinoma cells when DKK3 is used to inhibit the Wnt/ β -catenin pathway, 35 and increased si-LGR5-induced apoptosis when the mitochondrial membrane potential is disrupted in colorectal cancer cells. 36 In our study, significantly greater HC loss was observed in β -catenin knockout cochleae compared with controls after neomycin treatment ( Figure 2 ), which was accompanied by upregulation of the pro-apoptotic transcription factor Foxo3 and its downstream target gene Bim ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that curcumin increases MMC-mediated cell death in BCSCs by regulating Bcl-2 family protein expression via the mitochondria-dependent pathway. Furthermore, curcumin-treated BCSCs exhibited the typical features of apoptotic cell death, including shrinkage, transient phosphatidylserine exposure, increased membrane permeability, and a decrease in mitochondrial membrane potential [ 44 ]. In this study, the combination treatment of curcumin and MMC also reduced mitochondrial membrane potential in MCF-7 BCSCs by approximately 20% compared with the treatment with curcumin or MMC separately (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dkk3 activates or inhibits Wnt signaling in a tissue-dependent manner and its impact on cartilage Wnt signaling is unknown 7 , 8 , 9 . Dkk3 is a tumour suppressor that inhibits proliferation of cancer cells and is downregulated in several types of human cancer 8 , 9 , 10 . It can modulate inflammatory cell activity, maintain tissue organisation via TGFβ signaling and can protect against myocardial infarction-induced fibrosis 11 , 12 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%